A Study on Antibiotics Prescribing Pattern at Outpatient Department in Four Hospitals in Aden-Yemen - Alshakka, Mohammed; Said, Khaled; Babakri, Mohammed; Ansari, Mukhtar; Aldhubhani, Adel; Hassali, Mohamed Azmi; Mohamed Ibrahim, Mohammed Izham (Journal of Pharmacy Practice and Community Medicine)
Objective: The study was to investigate antibiotic prescription patterns at outpatient departments (OPDs) at four hospitals in Aden-Yemen. Settings and Design: A cross sectional descriptive study was conducted in the four hospitals in different areas of Aden city, the commercial capital of Yemen, from November 2015 through December 2015. WHO indicators were chosen. The study sampled the prescriptions conveniently. The data collection form used include Core Indicators and Complimentary Indicators of WHO such as average number of medicines per encounter, percentage of medicines prescribed by generic name, percentage of medicines prescribed from the EML and percentage of prescriptions in accordance with treatment guidelines. Data was analysed descriptively. Results: Out of the 400 prescriptions received from the outpatient clinics in the four hospitals during the study period, 337 antibiotic prescriptions were counted for. The percentage of prescriptions involving antibiotics was 84.2%. The average number of drugs per prescription was 3.2. Out of the surveyed antibiotic prescriptions, 65% contain one antibiotic and more than one-third were in the cephalosporin group (38.8%). Generally, 41% of the prescriptions were generic, furthermore, 44.8% of the prescribed medicines across all hospitals were from the EML. Conclusion: Important number of the prescribing indicators showed deviation from the standard values recommended by WHO. This deviation indicated an obvious degree of irrational/inappropriate prescribing in the hospitals, particularly poly pharmacy, underuse of international nonproprietary names (generic names), and over prescription of antibiotics. The study recommended to more adherence to WHO antibiotic prescribing guidelines and improving knowledge of proper and good prescribing procedure among health system prescribers.
Keywords: Antibiotics; Hospital; Prescribing pattern; WHO indicators; Yemen